Chronic lymphoproliferative disorder of NK‐cells: A single‐institution review with emphasis on relative utility of multimodality diagnostic tools. (9th March 2018) - Kurt, Habibe; Jorgensen, Jeffrey L.; Amin, Hesham M.; Patel, Keyur P.; Wang, Sa A.; Lin, Pei; Kanagal‐Shamanna, Rashmi; Loghavi, Sanam; Thakral, Beenu; Khogeer, Haitham A.; Jabbour, Elias J.; Li, Shaoying; et al.
Abstract: Background: Chronic lymphoproliferative disorder of NK‐cells (CLPD‐NK) manifests as a persistent increase (≥2 × 10 9 /L, for > 6 months) of mature NK‐cells in peripheral blood with an indolent clinical course. The disease is rare, and only limited case series have been published. Methods: We retrospectively studied 11 patients with CLPD‐NK diagnosed at our institution between 2005 and 2017. Results: Patients included 7 men and 4 women with a median age of 60 years (range, 25‐89 years). Ten patients (91%) had cytopenias. Bone marrow involvement by CLPD‐NK ranged from 5‐15%. The most commonly detected antigenic aberrancies by low cytometry immunophenotyping were as follows: CD7 decreased/dim (30%), CD8 uniform+ (36%), CD56 −/partial (73%), CD94 bright (55%), and KIR restriction (100%). JAK/STAT pathway mutations were detected in 8 of 10 (80%) patients and involved STAT3 (n = 7) and JAK3 (n = 1). The presence of mutations tended to correlate with the occurrence of other cytopenias (anemia/thrombocytopenia) and requirement for treatment. Seven patients received single‐agent therapy, with amelioration of symptoms; 4 patients were observed. There were no disease‐associated deaths or progression to more aggressive disease during the follow‐up interval (median, 17 months). Conclusions: Patients with CLPD‐NK have an indolent clinical course and frequent hematologic manifestations that are responsive to single‐agent therapy. Mutations in STAT3 are common and portend more pronounced clinical manifestations.